Systems social marketing: a critical appraisal - Truong, V. Dao; Saunders, Stephen Graham; Dong, X. Dam (Journal of social marketing, 2019)
Purpose Social marketing has gained widespread recognition as a means of motivating behaviour change in individuals for societal good. Many opinions have been shared regarding its potential to affect society or systems-wide change, leading to the macro-or systems social marketing (SSM) concepts and ideas. This paper aims to critically appraise the SSM literature, identify key features and highlight gaps for future research. Design/methodology/approach A search was conducted of peer-reviewed SSM articles published from 2000 to March 2018 inclusive. A number of online databases were mined, including but not limited to Google, Google Scholar, Scopus, PubMed, Cochrane and Medline. Key social marketing outlets (Social Marketing Quarterly and Journal of Social Marketing) were browsed manually. In total, 28 SSM articles were identified. Findings SSM adopts a dynamic systems thinking approach; it is an orientation, not a theory or model; it is multi-method; and it recognises that intervention can occur on multiple levels. Yet, greater attention should be given to the complexities of the systems context and the power structures and relations that exist between stakeholders. Significant issues also include stakeholder voice and participation, the use and reporting of theories and models, the measurement of long-term intervention outcomes and the undesirable impacts of SSM. Originality/value This paper identifies issues that need to be addressed if social marketing is to become a more system-oriented means to positively influence societal change. Implications for theoretical and practical development of the social marketing field are provided.